The Total Flavonoid Content And Bioassay Test Characteristics Of Sorghum Extracts At Different Levels Of Drought Stress - Edi Susilo; Hesti Pujiwati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: to determine the total flavonoid content and seed germination characteristics in bioassay tests due to sorghum extracts' application at various drought stress levels. Extract materials were prepared from June to August 2024 at Bengkulu University Greenhouse, Kandang Limun Village, Bengkulu City, and bioassay tests were conducted in August 2024 at Pematang Gubernur, Muara Bangkahulu, Bengkulu City. Flavonoid analysis was performed at the Integrated Research and Testing Laboratory (LPPT) of Gadjah Mada University in August 2024. Methodology: This study used a completely randomized design (CRD) with one factor. Two sorghum varieties, Super 2 and Mandau, were planted with water stress treatment through watering patterns every day, every 3 days, and every 5 days. The experimental unit was a petri dish, and the experiment was repeated four times. The Petri dish bioassay method was applied in this experiment.Each petri dish was given 10 mL of water extract, and 25 mung bean seeds were planted and incubated for three days. Results: The results showed that the Mandau variety had the highest total flavonoid content with watering every 3 days (3991.34 µg/g), and the Super 2 variety had the lowest total flavonoid content with watering every day (3165.26 µg/g). The highest germination inhibition was achieved by the sorghum variety Mandau with watering every 5 days. The treatment produced the highest inhibition on the test plants, so it has the potential to be the best bioherbicide. Findings: The Mandau variety has the highest total flavonoid content with watering every 3 days, and the Super 2 variety has the lowest total flavonoid content with watering every day. Novelty: This study provides insight into the total flavonoid content and seed germination characteristics due to the application of sorghum extracts at various levels of drought stress. Originality: This study offers a detailed analysis of total flavonoid levels and seed germination characteristics in bioassay tests. Conclusion: The Mandau variety had the highest total flavonoid content with watering every 3 days. The Mandau sorghum variety achieved the highest germination inhibition with watering every 5 days. Type of Paper: empirical research article.